Implantable Doppler monitoring of buried free flaps during vascularized lymph node transfer. Issue 3 (25th April 2017) - Teven, Chad M.; Ooi, Adrian S. H.; Inbal, Amir; Chang, David W.
Abstract : Background and Objectives: Reliable flap monitoring is crucial to the success of free tissue transfer, including vascularized lymph node transfer (VLNT). However, no large‐scale study has examined implantable Doppler monitoring in VLNT. We aimed to determine whether an implantable Doppler system can reliably monitor flap perfusion during VLNT and also to calculate the sensitivity and specificity of this system for detecting compromise in the monitored vessel. Methods: An analysis of prospectively collected data of patients who underwent buried VLNT with implantable Doppler monitoring between 2014 and 2015 was performed. Results: A consecutive series of 100 patients underwent VLNT with implantable Doppler monitoring. Five cases required return to the operating room for flap exploration due to a change in Doppler signal quality. All compromised flaps were salvaged. The sensitivity of the implantable Doppler system for flap monitoring was 100%, the specificity was 97.9%, the positive predictive value was 60%, and the negative predictive value was 100%. The false‐positive rate was 2%. Conclusions: This is the largest reported series of implantable Doppler monitoring of free flap perfusion during VLNT. Our experience suggests that this is a safe and effective technique for postoperative monitoring of VLNT.